Review of the genus Pamirospila Wolf, 1970 (Hymenoptera, Pompilidae), with description of a new species - Loktionov, Valery M. (Zootaxa, 2024)
Seven species of the genus Pamirospila Wolf, 1970 are reviewed, of them, P. montana Loktionov, sp. nov., is newly described and illustrated from Tajikistan based on female. The new species is clearly distinguished from all congeners by the shape of the vertex. Diagnoses of the genus and species are clarified. Lectotype of Psammochares pamirus Haupt, 1930 is designated. A new combination is proposed for Pamirospila stjenkarasini (Wolf, 1977), comb. nov. An updated key to the species is provided.